Crafting Leaders in the Digital Age: How Adaptive Management Strategies Revolutionize Leadership Development in Islamic Schools - Dinda Febrianti Putri; Abdullah Abdullah; Maulidatul Hasanah; Maulidiyah Junnatul Azizah Heru; Muhammad Mushf El Iq Bali; Abdul Wahid Zaini (Communautaire: Journal of Community Service, 2024)
This study investigates the impact of adaptive organizational management on the development of student leadership skills in an Islamic educational setting. The primary objective is to explore how responsive and dynamic management strategies can enhance leadership capabilities among students, particularly within the context of SMA ISTIQLAL, a prominent Islamic high school in Probolinggo, Indonesia. The research adopts a qualitative approach, employing a case study methodology to provide a comprehensive understanding of the interactions between school management, students, and leadership programs. Data were collected through in-depth interviews, participatory observations, and document analysis involving school administrators, teachers, and students. The findings reveal that adaptive management practices significantly improve students' leadership skills by fostering an environment of active engagement, motivation, and responsibility. Moreover, the study highlights the importance of continuous feedback and the flexible adaptation of leadership programs to meet the evolving needs of students. The implications of this research suggest that educational institutions should consider integrating adaptive management strategies into their leadership development programs to better prepare students for future challenges